Hematopoietic Stem Cell Transplantation for CD40 Ligand Deficiency: Single Institution Experience. Issue 12 (20th August 2015) - Allewelt, Heather; Martin, Paul L.; Szabolcs, Paul; Chao, Nelson; Buckley, Rebecca; Parikh, Suhag
<x xml:space="preserve">Abstract</x> Background X‐linked hyper‐IgM syndrome (X‐HIGM) due to mutations in the gene encoding CD40 ligand results in failure of Ig class switching and an increased propensity for recurrent sinopulmonary and other infections, and thus decreased life expectancy. Allogeneic hematopoietic stem cell transplantation (HSCT) is curative, but long‐term follow‐up data are limited. Procedures We conducted a retrospective analysis of seven patients who have undergone allogeneic HSCT for HIGM syndrome at Duke University Medical Center. Results Median age at transplant was 5.2 years (range 0.7–19.3). None of the patients had active hepatic or pulmonary disease immediately prior to transplant, but all had a history of serious infections. Five patients received myeloablative conditioning, and two patients received reduced intensity conditioning. Graft sources included bone marrow, peripheral blood, and unrelated umbilical cord blood. Post‐transplantation complications included veno‐occlusive disease, hemorrhagic cystitis, adenoviremia, and cryptosporidium recurrence in one patient each. Two patients developed acute GVHD grades II–IV that resolved promptly with treatment and none developed extensive chronic GVHD. All patients are intravenous IgG‐independent and 6/7 have normal antibody titers. Immunoglobulin (Ig) A levels normalized in all but one patient and T and B cell numbers and function are otherwise normal in all. All patients are alive at a median follow‐up of 9.7 (range 9.7–16.1) years post‐transplantation with predominantly donor chimerism and no recurrent infections. Conclusions Allogeneic HSCT results in excellent survival and sustained immune reconstitution in patients with CD40 ligand deficiency using both myeloablative and reduced intensity conditioning approaches and various graft sources, including bone marrow, peripheral blood, and umbilical cord blood. Pediatr Blood Cancer 2015; 9999:XX–XX © 2015 Wiley Periodicals, Inc.